2021
DOI: 10.1021/acsmedchemlett.1c00001
|View full text |Cite
|
Sign up to set email alerts
|

Structural and in Vitro Functional Characterization of a Menthyl TRPM8 Antagonist Indicates Species-Dependent Regulation

Abstract: TRPM8 antagonists derived from its cognate ligand, (−)-menthol, are underrepresented. We determine the absolute stereochemistry of a well-known TRPM8 antagonist, (−)-menthyl 1, using VCD and 2D NMR. We explore 1 for its antagonist effects of the human TRPM8 (hTRPM8) orthologue to uncover species-dependent inhibition versus rat channels. (−)-Menthyl 1 inhibits menthol-and icilin-evoked Ca 2+ responses at hTRPM8 with IC 50 values of 805 ± 200 nM and 1.8 ± 0.6 μM, respectively, while more potently inhibiting agon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 32 publications
(75 reference statements)
1
6
0
Order By: Relevance
“…4e , p < 0.001 vs. wild-type), revealing a testosterone activity through TRPM8 in trigeminal neurons. Previous studies described structural and functional differences between murine and human TRPM8 35 . To evaluate this possibility, we assessed testosterone activity on HEK293 cells constitutively expressing murine or human TRPM8 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4e , p < 0.001 vs. wild-type), revealing a testosterone activity through TRPM8 in trigeminal neurons. Previous studies described structural and functional differences between murine and human TRPM8 35 . To evaluate this possibility, we assessed testosterone activity on HEK293 cells constitutively expressing murine or human TRPM8 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…IMR90 fibroblast-like cells (CCL-186 ATCC, Virgina, USA) were seeded in 12 mm coverslips at 50,000 cells/well and were maintained in MEM enriched with 10% FBS and 1% penicillin/streptomycin at 37 °C in 5% CO 2 atmosphere 88 . For the initial experiments assessing TRPM8 function, HEK293 cells constitutively expressing human or rat TRPM8 35 were obtained from Prof. Belmonte Laboratory (Instituto de Neurociencias, San Juan, Alicante, Spain). All calcium imaging and electrophysiological recordings took place when cells reached 60% of confluence and 72 h after transfection when applicable.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The menthol encapsulated into the experimental fibers after being dissolved in acetone, as for the cytotoxicity assays, induced intracellular Ca 2+ increases in a concentrationdependent fashion in treated HEK293-hTRPM8 cells (Figure 5). First, TRPM8 activation dynamics were determined for our experimental model using free menthol (Figure 5a,b), describing a dose-response curve as in previous works [49]. Follow-up studies showed that the menthol contained in both types of fibers was able to activate TRPM8 similarly, and also in a concentration-dependent manner (Figure 5c,d for F 119S and F 139S samples, respectively).…”
Section: Assessment Of the Activation Capacity Of Trpm8 By The Encaps...mentioning
confidence: 72%
“…The work of different academic groups also contributed to the identification of novel chemotypes that inhibit TRPM8 receptor activation. In a very recent paper, Journigan et al described a (-)-menthyl derivative 29 (Figure 6, Table 2) as a potent antagonist of TRPM8 channels [163]. Calcium imaging assays were carried out to assess the (−)-menthyl 29 species-dependent inhibition of both menthol-and icilin-mediated responses, at either human or rat TRPM8, using strictly the same experimental conditions.…”
Section: Trpm8 Antagonistsmentioning
confidence: 99%